2013
DOI: 10.5489/cuaj.318
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine for the treatment of post-prostatectomy stress urinary incontinence

Abstract: E260 research researchCite as: Can Urol Assoc J 2013;7(5-6):e260-2. http://dx.doi.org/10.5489/cuaj.318 Published online May 13, 2013. AbstractObjectives: Stress urinary incontinence (SUI) is a known complication following prostatectomy. Duloxetine, a combined serotonin/ norepinephrine reuptake inhibitor, can decrease SUI by increasing urethral sphincter contractility. We examined the outcomes of patients with mild to moderate post-prostatectomy SUI treated with duloxetine. Methods: We conducted a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
0
14
0
2
Order By: Relevance
“… 20 Further, duloxetine has been approved in Europe as a treatment for stress urinary incontinence in females for over a decade. 21 …”
Section: Discussionmentioning
confidence: 99%
“… 20 Further, duloxetine has been approved in Europe as a treatment for stress urinary incontinence in females for over a decade. 21 …”
Section: Discussionmentioning
confidence: 99%
“…2013 yılında yapılan diğer bir çalışmada hafif-orta derecede idrar kaçırması (≤5 ped/gün) olan 94 postprostatektomi inkontinans hastası çalışmaya dahil edilmiş ve 1 ay süreyle 60 mg duloksetin tedavisi sonrası yaşam kalitesi skorlarında, tatmin skorlarında ve günlük ped kullanımında anlamlı derecede iyileşme olduğu görülmüştür. Hastaların %54'ünde günlük ped kullanımının yarı yarıya azaldığı gözlemlenmiştir (31). Ülkemizden yapılan bir çalışmada ise laparoskopik radikal prostatektomi sonrası inkontinası olan 60 hasta duloksetin ve PTE+duloksetin olmak üzere 2 gruba randomize edilmiştir.…”
Section: Discussionunclassified
“…Three studies examined SUI in patients treated with duloxetine, and both demonstrated that duloxetine improved postprostatectomy SUI up to 3 months postsurgery, but the benefits were not sustained in one of these studies up to 24 weeks (~5 months) 78, 91, 93. In addition, the drug intolerance and dropout rates are ~15–35% with duloxetine after ≥ 1 month of use 78, 93.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the drug intolerance and dropout rates are ~15–35% with duloxetine after ≥ 1 month of use 78, 93.…”
Section: Discussionmentioning
confidence: 99%